Epistemic Values of Islamic Law in Green Financing Contracts - Inayati, Anindya Aryu; Rahman, Muhammad Fazlur; Saleh, Hairus (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
TThis research aims to describe the epistemic values of Islamic Law in green financing contracts. The research design used in this research is descriptive qualitative research with a philosophical approach. Regarding the data collection, this study uses the library method with a systematic literature review analysis. The findings show that green financing contracts are business financing contracts that have special conditions, specifically a dedication to going green, conserving the environment, and safeguarding wildlife. The epistemic values of Islamic Law in green financing contracts are transcendence, maslaha, al-islah and humanist values. This study is the first to assess epistemic values in green financing, as far as the author knows. Therefore, this research might provide significant recommendations on green finance for financial institutions and its epistemological objectives